2022
DOI: 10.1017/jfm.2022.506
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance growth on a NACA0008 wing subjected to free stream turbulence

Abstract: The stability of an incompressible boundary layer flow over a wing in the presence of free stream turbulence (FST) has been investigated by means of direct numerical simulations and compared with the linearised boundary layer equations. Four different FST conditions have been considered, which are characterised by their turbulence intensity levels and length scales. In all cases the perturbed flow develops into elongated disturbances of high and low streamwise velocity inside the boundary layer, where their sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…For instance, Brandt et al (2004) reported that small-scale fluctuations penetrated easier into the boundary layer than large-scale fluctuations, while large-scale fluctuations were more dominant in fluctuation growing downstream. Similar results were obtained by recent DNSs on wing surfaces (Faúndez Alarcón et al, 2022) and on a flat plate (Mamidala et al, 2022). Nakagawa et al (2023a) also reported the wavelength dependency in the swept flat plate boundary layer.…”
Section: Introductionsupporting
confidence: 88%
“…For instance, Brandt et al (2004) reported that small-scale fluctuations penetrated easier into the boundary layer than large-scale fluctuations, while large-scale fluctuations were more dominant in fluctuation growing downstream. Similar results were obtained by recent DNSs on wing surfaces (Faúndez Alarcón et al, 2022) and on a flat plate (Mamidala et al, 2022). Nakagawa et al (2023a) also reported the wavelength dependency in the swept flat plate boundary layer.…”
Section: Introductionsupporting
confidence: 88%
“…Previous investigations have already used Nek5000 to study the effect of FST in transition. Those studies include, for instance, the effect of the FST characteristics in bypass transition on a wing section (Faúndez Alarcón et al 2022), the interaction between FST and surface roughness on a swept wing (De Vincentiis, Henningson & Hanifi 2022), and FST-induced transition on a low-pressure turbine where comparison against experimental measurements are available (Durovic et al 2021).…”
Section: Datasetmentioning
confidence: 99%